Making Subsidies Work: Rules vs. Discretion - Federico Cingano; Filippo Palomba; Paolo Pinotti; Enrico Rettore (Center for Economic Studies and ifo Institute (CESifo), 2022)
We estimate the effects of a large program of public investment subsidies granted to Italian firms in disadvantaged areas. Projects were given numerical scores according to objective criteria and local politicians' preferences, and funded in rank order until the funds were fully allocated. We estimate that subsidies increased investment by marginal firms near the cutoff by 39 percent, and employment by 17 percent over a 6-year period. Building on recent advancements in the econometrics of regression discontinuity designs, we characterize heterogeneity of treatment effects and cost-per-new-job across inframarginal firms away from the cutoff. Employment grows more in smaller firms, but larger firms generated more jobs-per-euro of subsidy. Younger firms did better than older firms. Firms ranking high on objective criteria and firms preferred by local politicians generated larger employment growth on average, but the latter did so at a higher cost per job. Under a policy invariance assumption, we estimate that eliminating political discretion and relying only on objective criteria would reduce the cost per job by 9 percent, while relying only on political discretion would increase the cost by 55 percent. The effect of political discretion is larger in the south, which received the largest share of funds and exhibited the highest cost-per-job under the actual allocation criteria.
Keywords: H25; J08; 330; public subsidies; investment; employment; political discretion; regression discontinuity